EVALUASI IMPLEMENTASI KURIKULUM BAHASA ARAB DI PONDOK PESANTREN SALAFIYAH DAN MODERN - Sapura, Najla Lia; Amalia, Lia; Shofah, Anuri; Nugraha, Rahmat Mulya (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
Curriculum evaluation is a strategic step in improving the quality of learning, including in teaching Arabic in Islamic boarding schools. This article discusses the evaluation of the Arabic language curriculum in Salafiyah and modern Islamic boarding schools using the CIPP (Context, Input, Process, Product) model developed by Daniel Stufflebeam. This model allows for a comprehensive assessment of the curriculum context, resources, learning implementation, and the final results achieved. Salafiyah Islamic boarding schools emphasize more on understanding classical texts (yellow books) with traditional methods such as sorogan and bandongan, while modern Islamic boarding schools adopt a competency-based and technology-based approach to improve active communication skills in Arabic. The evaluation shows that both types of Islamic boarding schools have their own advantages and challenges in implementing the Arabic language curriculum. Supporting factors such as the competence of teaching staff, the use of learning media, and policy support also influence the effectiveness of the curriculum. Therefore, a comprehensive evaluation system is needed so that Islamic boarding schools can develop a curriculum that is relevant. ABSTRAKEvaluasi kurikulum merupakan langkah strategis dalam meningkatkan kualitas pembelajaran, termasuk dalam pengajaran bahasa Arab di pesantren. Artikel ini membahas evaluasi kurikulum bahasa Arab di pesantren salafiyah dan modern dengan menggunakan model CIPP (Context, Input, Process, Product) yang dikembangkan oleh Daniel Stufflebeam. Model ini memungkinkan penilaian menyeluruh terhadap konteks kurikulum, sumber daya, pelaksanaan pembelajaran, dan hasil akhir yang dicapai. Pesantren salafiyah lebih menitikberatkan pada pemahaman teks klasik (kitab kuning) dengan metode tradisional seperti sorogan dan bandongan, sementara pesantren modern mengadopsi pendekatan berbasis kompetensi dan teknologi untuk meningkatkan kemampuan komunikasi aktif dalam bahasa Arab. Evaluasi menunjukkan bahwa kedua jenis pesantren memiliki keunggulan dan tantangan masing-masing dalam implementasi kurikulum bahasa Arab. Faktor pendukung seperti kompetensi tenaga pengajar, penggunaan media pembelajaran, dan dukungan kebijakan turut memengaruhi efektivitas kurikulum. Oleh karena itu, dibutuhkan sistem evaluasi yang komprehensif agar pesantren dapat menyusun kurikulum yang relevan.